The use of first-generation cephalosporin antibiotics, cefalexin and cefradine, is not associated with induction of simulated Clostridioides difficile infection. (25th September 2021) - Buckley, Anthony M; Moura, Ines B; Altringham, James; Ewin, Duncan; Clark, Emma; Bentley, Karen; Wilkinson, Vikki; Spittal, William; Davis, Georgina; Wilcox, Mark H
Abstract: Objectives: The use of broad-spectrum cephalosporins is associated with induction of Clostridioides difficile infection (CDI). Recent knowledge on the importance of the healthy microbiota in preventing pathogen colonization/outgrowth highlights the caution needed when prescribing broad-spectrum antibiotics. The use of historical narrow-spectrum antibiotics, such as first-generation cephalosporins, is gaining increased attention once more as they have a reduced impact on the microbiota whilst treating infections. Here, the effects of two first-generation cephalosporins, compared with a third-generation cephalosporin, on the human microbiota were investigated and their propensity to induce simulated CDI. Methods: Three in vitro chemostat models, which simulate the physiochemical conditions of the human colon, were seeded with a human faecal slurry and instilled with either narrow-spectrum cephalosporins, cefalexin and cefradine, or a broad-spectrum cephalosporin, ceftriaxone, at concentrations reflective of colonic levels. Results: Instillation of cefalexin was associated with reduced recoveries of Bifidobacterium and Enterobacteriaceae; however, Clostridium spp. recoveries remained unaffected. Cefradine exposure was associated with decreased recoveries of Bifidobacterium spp., Bacteroides spp. and Enterobacteriaceae. These changes were not associated with induction of CDI, as we observed a lack of C. difficile spore germination/proliferation, thus no toxin was detected. This is in contrast to a model exposed to ceftriaxone, where CDI was observed. Conclusions: These model data suggest that the minimal impact of first-generation cephalosporins, namely cefalexin and cefradine, on the intestinal microbiota results in a low propensity to induce CDI.